Higher education and SDG11 : sustainable cities and communities - Lumbreras, Julio; Moreno-Serna, Jamie (Higher education and the sustainable development goals, 2024)
What role can higher education play to foster and support sustainable cities and communities? Emerging amidst one of the most decisive moments in our planet's history, Higher Education and SDG11 is a powerful call to action for the development of multi-stakeholder collaborations to address the challenges of sustainable development in urban environments and communities. Conscious of the urgent need for the transformation of our urban systems at the scale outlined by the 2030 Sustainable Development Goals (SDGs), the chapters in this edited collection position universities as anchor institutions, reinforcers of the convening capacity to create, nurture, and scale-up research, transfer, and education capabilities. Showcasing practical cases from Europe, Africa, and the Americas, contributors promote new ways of participation, encouraging higher education institutions (HEIs) and their students to play an intermediary role within their local communities and co-create ways to help foster urban sustainable development. Articulating a shared vision of climate-neutral cities, Higher Education and SDG11 asserts the unique position of HEIs to facilitate and unlock the much-needed alignment of research and education with SDG-oriented action. Higher Education and the Sustainable Development Goals is a series of 17 books that address each of the SDGs through the lens of higher education. Adopting a solutions-based approach, each book focuses on how higher education is advancing delivery of Agenda 2030. The series is edited by Wendy Purcell, Professor with Rutgers University and Academic Research Scholar with Harvard University; Emeritus Professor and University President Emerita.